Utilizing the Dyn2 dimerization-zipper as a tool to probe NPC structure and function - Flemming, Dirk; Stelter, Philipp; Hurt, Ed (Nuclear pore complexes and nucleocytoplasmic transport, 2014)
The discovery of dynein light chain 2 (Dyn2) as a member of the nucleoporins in yeast led to a series of applications to study NPC structure and function. Its intriguing ability to act as a hub for the parallel dimerization of two short amino acid sequence motifs (DID) prompted us to utilize it as a tool for probing nucleocytoplasmic transport in vivo. Further, the distinct structure of the Dyn2-DID rod, which is easily visible in the electron microscope, allowed us to develop a precise structural label on proteins or protein complexes. This label was used to identify the position of subunits in NPC subcomplexes or to derive at pseudo-atomic models of single large Nups. The versatility for various applications of the DID-Dyn2 system makes it an attractive molecular tool beyond the nuclear pore and transport field.
Gesehen am 30.09.2020